A systematic review of metabolomic studies of childhood obesity: State of the evidence for metabolic determinants and consequences. (19th November 2021) - Handakas, Evangelos; Lau, Chung Ho; Alfano, Rossella; Chatzi, Vaia Lida; Plusquin, Michelle; Vineis, Paolo; Robinson, Oliver
Summary: Childhood obesity has become a global epidemic and carries significant long‐term consequences to physical and mental health. Metabolomics, the global profiling of small molecules or metabolites, may reveal the mechanisms of development of childhood obesity and clarify links between obesity and metabolic disease. A systematic review of metabolomic studies of childhood obesity was conducted, following Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines, searching across Scopus, Ovid, Web of Science and PubMed databases for articles published from January 1, 2005 to July 8, 2020, retrieving 1271 different records and retaining 41 articles for qualitative synthesis. Study quality was assessed using a modified Newcastle–Ottawa Scale. Thirty‐three studies were conducted on blood, six on urine, three on umbilical cord blood, and one on saliva. Thirty studies were primarily cross‐sectional, five studies were primarily longitudinal, and seven studies examined effects of weight‐loss following a life‐style intervention. A consistent metabolic profile of childhood obesity was observed including amino acids (particularly branched chain and aromatic), carnitines, lipids, and steroids. Although the use of metabolomics in childhood obesity research is still developing, the identified metabolites have provided additional insight into the pathogenesis of many obesity‐related diseases. Further longitudinal research is needed into the role of metabolic profiles and child obesity risk.